The Massachusetts Infertility Insurance Mandate: not nearly enough - Katherine G. Koniares, M.D; Alan S. Penzias, M.D; James Roosevelt, Jr., J.D; Eli Y. Adashi, M.D., M.S (Elsevier, 2022)
Objective: To assess the impact of statutory federal and state exceptions to the state law mandating insurance coverage for the diagnosis and treatment of infertility. Design: Population-based cross-sectional study comprised of reproductive-age women (defined herein as 20-44 years of age) who resided in Massachusetts during the 2016-2019 interval. Statutory exemptions to the benefits afforded by the Massachusetts Infertility Insurance Mandate were identified in the Massachusetts General Laws as well as in the United States Code. Setting: Not applicable. Patient(s): Publicly available, deidentified, population-level data pertaining to state-based reproductive-age women (aged 20-44 years) were procured for the 2016-2019 interval. Data sources included the Massachusetts Census Bureau, Massachusetts Center for Health Information and Analysis, US Department of Defense, and US Office of Personnel Management. Intervention(s): None. Main Outcome Measure(s): The proportion of state-based reproductive-age women who constitute beneficiaries of the Massachusetts Infertility Insurance Mandate after accounting for the applicable state and federal statutory exemptions that limit its impact. Result(s): Public health plans (Medicare, MassHealth [state Medicaid], TRICARE, and the Federal Employees Health Benefits Program) are exempted from the Massachusetts Infertility Insurance Mandate by dint of federal or state statute. Self-insured employer-sponsored health plans are exempted from the Massachusetts Infertility Insurance Mandate by dint of the federal Employee Retirement Income Security Act. It follows that only 26.2%-36.0% of state-based reproductive-age women comprised eligible beneficiaries of the Massachusetts Infertility Insurance Mandate over the 2016-2019 interval. Conclusion(s): Contrary to commonly held views, multiple statutory exemptions to the Massachusetts Infertility Insurance Mandate render a significant proportion of state-based reproductive-age women ineligible for its cognate benefits. We propose herein that the Essential Health Benefit categories of the Affordable Care Act be expanded by the US Congress to include infertility care services.